Transit-oriented development in the Greater Copenhagen Region: Insights from small- and medium-sized cities. - Grunfelder, Julien; Lidmo, Johannes; Huynh, Diana (My University, 2020)
How can an enhanced understanding of transit-oriented development (TOD) characteristics and mobility planning in small- and medium-sized (SMS) cities contribute to a more integrated Greater Copenhagen Region? Also, what are the multi-functional roles and potentials for the development of areas surrounding railway stations in small- and medium-sized cities from a planning and design perspective?  Answering these questions is the main purpose of this study that has been conducted by Nordregio on behalf of the Nordic thematic group for sustainable cities and urban development 2017– 2020 and its cross-border member Greater Copenhagen Region (GCR). It explores the concept of TOD, accessibility by train, as well as TOD-characteristics and mobility planning in the context of the GCR. This cross-border region is composed of four administrative regions: the Capital Region of Denmark (Hovedstaden) and Region Zealand on the Danish side, and Region Skåne and Region Halland on the Swedish side of the Öresund strait. This study is based on desk research, accessibility mapping, and semi-structured interviews in four selected municipalities (Lejre and Ringsted in Denmark and Höör and Landskrona in Sweden). Our research describes how accessible these four cases are within a local, regional and cross-border context. A particular focus is on the past, present and future plans in the station vicinity areas in order to highlight planning and design specificities of transit-oriented developments.
Keywords: Regionalverkehr; Ballungsraum; Grenzüberschreitender Verkehr; ÖPNV; Haltestelle; Erreichbarkeit; Siedlungsentwicklung; Nachhaltige Raumentwicklung; Verflechtungsraum; Pendlerverkehr; Großstadtregion; Stadtumland; Kleinstadt